THE APPLICATION OF "ROY ADAPTATION" THEORY MODEL IN WOMEN WITH EARLY STAGE OF CERVICAL CANCER: A STUDY CASE - Ida Maryati; Sukmawati S; Lilis Mamuroh (Journal of Maternity Care and Reproductive Health, 2018)
Women who diagnosed with cervical cancer face complex problems including physiological, psychological, social, and spiritual problems. Women are required to adapt to these complex problems. Nurses as part of health care providers have responsibilities to help clients in dealing with their conditions. Another role of nurses is to assist clients to meet their basic needs. Nurses provide nursing care using a variety of nursing theories so that the nursing care provided is optimal. One of the nursing theory is Roy's adaptation model, this model is one of theory as a foundation in providing nursing care. The aimed of the theory application was to apply the Roy theory, and it also expected that women with early-stage cervical cancer could adapt to their conditions. Method: The design of this study was a case study approach of five cases of a cervix. Roy's adaptation model applied effectively to early-stage of cervical cancer clients, as a result, clients adapt to changes that occur including physiologically, psychologically, socially, and spiritually. Roy's adaptation model would be more effective if it applies in combination with other concepts, especially theories about self-concept and social support to the nursing care provided would be more optimal.Keywords: cervical cancer, early stage, Roy's adaptation model